Do athletes need more dietary protein and amino acids? - Lemon, P. W. (International Journal of Sport Nutrition and Exercise Metabolism, 1995)
The current recommended daily allowance (RDA) for protein is based primarily on data derived from subjects whose lifestyles were essentially sedentary. More recent well-designed studies that have employed either the classic nitrogen balance approach or the more technically difficult metabolic tracer technique indicate that overall protein needs (as well as needs for some specific individual amino acids) are probably increased for those who exercise regularly. Although the roles of the additionally required dietary protein and amino acids are likely to be quite different for those who engage in endurance exercise (protein required as an auxiliary fuel source) as opposed to strength exercise (amino acids required as building blocks for muscle development), it appears that both groups likely will benefit from diets containing more protein than the current RDA of 0.8 g/kg/day. Strength athletes probably need about 1.4-1.8 g/kg/day and endurance athletes about 1.2-1.4 g/kg/day.